Quality of and access to green space in relation to psychological distress: results from a population-based cross-sectional study as part of the EURO-URHIS 2 project. (15th July 2015) - Pope, D; Tisdall, R; Middleton, J; Verma, A; van Ameijden, E; Birt, C; Macherianakis, A; Bruce, N G
Abstract: Background: Psychological distress (PD) (mental ill-health) has a frequency between 5 and 25% in urban populations, and there is mounting evidence that access to green space might reduce its occurrence. Evidence suggests that the quality of green space is as important as accessibility in promoting mental well-being. A pilot study for EURO-URHIS 2 allowed investigation of access to green space in relation to PD in a deprived urban population in the UK. Methods: An adult urban health indicator questionnaire, including the GHQ-12 and validated questions on access to and quality of green space, was sent to a stratified random sample of 1680 adults drawn from one general practice list in Sandwell, UK. Multivariable logistic regression was used to determine associations between attributes of green space and PD adjusting for age, sex and levels of deprivation. Results: There were 578 (35%) completed responses. The reported prevalence of PD [ n = 131 (22.7%)] was significantly greater than national England and Wales estimates. As well as accessibility (OR = 0.58; 95% CI = 0.35, 0.96) and sufficiency (OR = 0.12; 95% CI = 0.39, 0.89) of green spaces, having the ability to use them for relaxation and recreation were significantly associated with reduced PD [OR = 0.13 (0.42, 0.94) and OR = 0.11 (0.34, 0.80), respectively]. In addition, a dose–response relationship between number of positive green space attributes and PD was identified ( P < 0.05). Conclusion: This population-based study in a deprived urban UK population demonstrates an association, and some dose–response relationship, between access to and quality of green spaces with reduced PD. The cross-sectional design and use of subjective measures limit interpretation of causality. More knowledge is needed on how UK planning affects green spaces and the potential mental health consequences.